Collaborative Governance Dalam Program Pengembangan Nilai Budaya Daerah Melalui Banyuwangi Ethno Carnival - Harmawan, Bagus Nuari; Wasiati, Inti; Rohman, Hermanto (e-Sospol, 2017)
Abstract This study aims to describe collaborative governance in development program of local cultural values through Banyuwangi Ethno Carnival. The research used descriptive research type with qualitative approach and applied two types of data, namely primary data obtained from interview and observation and secondary data collected by documentation and literature study. Interviews were conducted with the parties involved in the problems to be analyzed. The data that had been collected were to be the information for the answer to the interview in this research. The data and information obtained showed that the stakeholders involved in BEC from 2011 to 2014 were Disbudparda (Department of Local Culture and Tourism) of Banyuwangi, JFC Management, Blambangan Arts Council and Carnival Instructors. In general, there were two patterns of cooperation in BEC event i.e. Public Private Partnership Pattern in 2011 and in 2012 until 2014. Barriers in building Collaborative Governance occurred in cultural and institutional factors.